Implementation of the 'Removed Injectable modified Short-course regimens for EXpert Multidrug Resistant Tuberculosis' (RISE study) in Tanzania: a protocol for a mixed-methods process evaluation. Issue 5 (24th May 2022) - Kalolo, Albino; Lalashowi, Julieth; Pamba, Doreen; Shayo, Pendomartha Joseph; Gitige, Catherine; Mvungi, Happiness; Ntagazwa, Webhale; Lekule, Isaac; Kisonga, Riziki; Mleoh, Liberate; John, Johnson; Kapologwe, Ntuli A; et al.
Abstract : Introduction: Tanzania is adapting a shortened injectable-free multidrug resistant tuberculosis (MDR-TB) regimen, comprising new drugs such as bedaquiline and delamanid and repurposed drugs such as clofazimine and linezolid. The regimen is implemented using a pragmatic prospective cohort study within the National TB and Leprosy Programme and is accompanied by a process evaluation. The process evaluation aims to unpack the implementation processes, their outcomes and the moderating factors in order to understand the clinical effectiveness of the regimen. This protocol describes the methods employed in understanding the implementation processes of the new MDR-TB regimen in 15 regions of Tanzania. Methods: This study adopts a concurrent mixed-methods design. Using multiple data collection tools, we capture information on: implementation outcomes, stakeholder response to the intervention and the influence of contextual factors. Data will be collected from the 22 health facilities categorised as dispensaries, health centres, district hospitals and referral hospitals. Health workers (n=132) and patients (n=220) will fill a structured questionnaire. For each category of health facility, we will conduct five focus group discussions and in-depth interviews (n=45) for health workers. Participant observations (n=9) and review documents (n=22) will be conducted using structured checklists. Data will be collected at two points over a period of 1 year. We will analyse quantitative data using descriptive and inferential statistical methods. Thematic analysis will be used for qualitative data. Ethics and dissemination: This study received ethical approval from National Institute of Medical research (NIMR), Ref. NIMR/HQ/R.8a/Vol.IX/3269 and from the Mbeya Medical Research and Ethics Review Committee, Ref. SZEC-2439/R.A/V.I/38. Our findings are expected to inform the wider implementation of the new MDR-TB regimen as it is rolled out countrywide. Dissemination of findings will be through publications, conferences, workshops and implementation manuals for scaling up MDR-TB treatments.